2009
DOI: 10.1354/vp.08-vp-0273-p-fl
|View full text |Cite
|
Sign up to set email alerts
|

Reduced PTEN Protein Expression and Its Prognostic Implications in Canine and Feline Mammary Tumors

Abstract: Abstract. Phosphatase and tensin homolog (PTEN) belongs to the group of gatekeeper tumor suppressor genes and is involved in multiple mechanisms leading to cellular defense against neoplastic transformation and progression. Twenty-four dogs and 17 cats were submitted to a 2-year follow-up study, and clinicopathologic features were recorded and compared with immunohistochemical PTEN staining. PTEN-negative status occurred in 33% of canine and 76% of feline mammary carcinomas. In canine mammary carcinomas, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 41 publications
4
27
1
1
Order By: Relevance
“…The results of the study about PTEN protein expression in this study were similar to those previously reported in human (Li et al, 1997;Bose et al, 2002) and veterinary (Kanae et al, 2006;Qiu et al, 2008;Ressel et al, 2009) literature. PTEN protein expression was positively correlated with clinico-pathological parameters commonly associated with a favorable prognosis, such as a complex histotype, the absence of lymphatics invasion and a longer overall survival, as previously reported for canine mammary tumours (Ressel et al, 2009).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the study about PTEN protein expression in this study were similar to those previously reported in human (Li et al, 1997;Bose et al, 2002) and veterinary (Kanae et al, 2006;Qiu et al, 2008;Ressel et al, 2009) literature. PTEN protein expression was positively correlated with clinico-pathological parameters commonly associated with a favorable prognosis, such as a complex histotype, the absence of lymphatics invasion and a longer overall survival, as previously reported for canine mammary tumours (Ressel et al, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…PTEN protein expression was positively correlated with clinico-pathological parameters commonly associated with a favorable prognosis, such as a complex histotype, the absence of lymphatics invasion and a longer overall survival, as previously reported for canine mammary tumours (Ressel et al, 2009). Regarding E-cadherin expression, in our study an altered expression was observed in malignant tumours when compared with benign ones, and in simple carcinomas when compared with complex type.…”
Section: Discussionsupporting
confidence: 88%
“…in dogs with osteosarcoma (37), melanoma (31), hemangiosarcoma (14) and mammary gland tumors (30,52,53). The loss of PTEN protein expression can be a useful marker in identifying mammary gland carcinoma in dogs (54).…”
mentioning
confidence: 99%
“…4,34 The Elston and Ellis (EE) histologic grading system (also known as the Nottingham Grading System) has been widely adopted by veterinary investigators for the grading of feline mammary carcinoma. 2,4,19,28,[32][33][34]40 This system represents the ''gold standard'' in assessment of invasive human breast cancer, whereby distinct histopathologic features (ie, percentage tubule formation, nuclear pleomorphism, and mitotic count) are scored and added together to produce a grade, which then correlates with degree of malignancy and prognosis. 8,30,31 Use of this grading system by veterinary pathologists is based primarily on evidence suggesting that feline mammary carcinoma represents a suitable model for human * Indicates equal contribution 1 breast cancer, particularly the more aggressive estrogennegative carcinomas.…”
mentioning
confidence: 99%